2018
DOI: 10.1016/j.biochi.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The binding efficiency of RPA to telomeric G-strands folded into contiguous G-quadruplexes is independent of the number of G4 units

Abstract: Replication protein A (RPA) is a single-stranded DNA binding protein involved in replication and in telomere maintenance. During telomere replication, G-quadruplexes (G4) can accumulate on the lagging strand template and need to be resolved. It has been shown that human RPA is able to unfold a single G4. Nevertheless, the G-strand of human telomeres is prone to fold into higher-order structures formed by contiguous G-quadruplexes. To understand how RPA deals with these structures, we studied its interaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…If the G4 sequences successfully fold into G4 structures, we speculated that some of those preformed G4s may be directly overcome by RPA as shown in Figure 8, scheme 2. In fact, RPA was known to unfold preformed G4 with the 5 0 -3 0 polarity from the studies of the Saintomé group (Salas et al, 2006;Safa et al, 2014Safa et al, , 2016Lancrey et al, 2018). Further studies revealed that the trimerization core of RPA is responsible for disrupting G4s by interacting with Guanines (Prakash et al, 2011a(Prakash et al, , 2011b.…”
Section: Rpa May Significantly Suppress G4 Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…If the G4 sequences successfully fold into G4 structures, we speculated that some of those preformed G4s may be directly overcome by RPA as shown in Figure 8, scheme 2. In fact, RPA was known to unfold preformed G4 with the 5 0 -3 0 polarity from the studies of the Saintomé group (Salas et al, 2006;Safa et al, 2014Safa et al, , 2016Lancrey et al, 2018). Further studies revealed that the trimerization core of RPA is responsible for disrupting G4s by interacting with Guanines (Prakash et al, 2011a(Prakash et al, , 2011b.…”
Section: Rpa May Significantly Suppress G4 Formationmentioning
confidence: 99%
“…In contrast, RPA1 mutation provokes the accumulation of those G-rich structures and the recruitment of homologous recombination factors ( Audry et al., 2015 ). Besides preventing G4 formation, RPA was also reported to disrupt the folded G4 structures in the 5′–3′ polarity ( Salas et al., 2006 ; Safa et al., 2014 , 2016 ; Lancrey et al., 2018 ). RPA trimerization core preferentially recognizes G4 or G-rich DNA, likely responsible for unfolding G4s ( Prakash et al., 2011a , 2011b ).…”
Section: Introductionmentioning
confidence: 99%
“…RPA binds and unfolds G4s under physiologically relevant conditions in vitro ( Salas et al, 2006 ; Qureshi et al, 2012 ; Ray et al, 2013 ). It unwinds G4 from 5′ to 3′, and this unwinding is independent of the number of G4 units ( Safa et al, 2016 ; Lancrey et al, 2018 ). Interestingly, Wu et al, recently showed that HERC2, a HECT E3 ligase, facilitates BLM (Bloom syndrome helicase) and WRN (Werner syndrome helicase) interaction with RPA and plays a critical function in suppressing G4 formation ( Wu et al, 2018 ; Figure 2C ).…”
Section: Rpamentioning
confidence: 99%
“…RPA consists of three subunits: replication protein A 70 kDa or DNA-binding subunit (RPA1); replication protein A 32 kDa subunit (RPA2); and replication protein A 14 kDa subunit (RPA3) [P27694, P15927, P35244 UniProt]. It is believed that the RPA complex involved in DNA metabolism and may also play a role in telomere maintenance by interacting with some telomere components, including shelterin [133,134,135,136]. For example, it has been shown that RPA, when interacting with single-strand telomeric DNA, acts as an antagonist to the POT1 protein and, thus, ensures DNA replication during the cell cycle while preventing the start of telomere elongation [27,133].…”
Section: Human Telomeres and Their Relationship With Some Hnrnps Imentioning
confidence: 99%